STUDY OF ADHESION ACTIVITY GEL COMPOSITIONS TRIMECAINE - A. M. Sampiev; A. V. Bespalova; E. B. Nikiforova (Кубанский научный медицинский вестник, 2016)
Local anesthesia is an integral component of medical procedures in today's children's dental practice. Enumeration of intraoral drugs containing anesthetics, for pediatric dentistry is extremely insufficient. Urgent is the development of children and of the dental gel containing trimekain, for application anesthesia. The purpose of this study was to study the adhesive properties of comparative gel compositions containing various combinations and trimekain potential of shaping. The studies revealed gel compositions with excellent adhesion characteristics, which can be recommended for further screening on the creation of children's dental gel trimecaine.